Медійна жанрологія в сучасній науці: лінгвістична постановка питання - Дергач, Дмитро Валерійович (Київський національний університет імені Тараса Шевченка, 2015)
З'ясовується специфіка лінгвістичного опрацювання жанрів масової інформації. Окреслюються основні проблеми, завдання, напрямки нової галузі мовознавчого знання – медійної жанрології. Визначаються перспективи мовознавчого вивчення жанрової парадигми сучасних ЗМІ.

The research attention is paid to the linguistic aspect of analysis of genres in modern mass-media sphere. The author determines the main tasks, issues and trends of new branch of linguistic knowledge – theory of mass-media genres. The perspective of such scientific problems is also outlined in the article, especially in correlation with dynamic, diffuse organization of mass media genres, with particular attention to their transformations as a result of evolutionary resource of literary language, comparable with the format and tasks of social / mass communication.
Theory of media genres in the modern science: linguistic aspect
Keywords: мас-медіа; жанр; медійна жанрологія; лінгвістична проблематика; mass-media; genre; theory of media genres; linguistic aspect